Feeding Level of Ewets in Different Physiological Conditions - Popova V. V.; Klichev Zafar Safarovich (International Journal on Orange Technologies, 2022)
The results of studies on the level of feeding of ewes under different physiological conditions are presented. Feeding norms for pregnant, suckling and single queens have been established.